Conversion of tannery solid waste to an adsorbent for high-efficiency dye removal from tannery wastewater: A road to circular utilization. (January 2021) - Tang, Yuling; Zhao, Jieting; Zhang, Yingjiao; Zhou, Jianfei; Shi, Bi
Abstract: The high value-added use of tannery solid waste and elimination of tannery liquid waste in the leather-making industry have attracted widespread attention. In this study, a MgO-doped biochar (MgO/BC) adsorbent was successfully prepared by utilizing tannery solid waste (i.e., non-tanned hide wastes) as the biomass material for dye removal from tannery wastewater. Characterization results indicated that MgO was uniformly embedded into the porous BC structure. The adsorption capacity of acid orange II by MgO/BC reached up to 448.4 mg g −1, which drastically exceeded the pure BC and other reported adsorbents. The adsorption behavior of acid orange II by MgO/BC matched nicely with Langmuir isotherm and pseudo-second-order kinetic model. This satisfactory adsorption capacity of MgO/BC for acid orange II was mainly due to the large specific surface area and the enhanced electrostatic interaction. According to the BET, zeta potential and XPS analysis, the possible mechanism towards acid orange II removal was attributed to the pore filling, surface complexation, electrostatic attraction and π-π interaction. In addition, MgO/BC showed the efficient removal towards anionic dyes from actual tannery wastewater. This work could provide guidance for the value-added utilization of tannery solid waste and a practical way to remove dyes from tannery wastewater. Graphical abstract: Image 1 Highlights: A MgO-doped biochar (MgO/BC) was prepared by utilizing tannery solid waste. The qmax of MgO/BC was 448.4 mg g −1, which was about 2 times that of BC. The introduction of MgO provided a positive charge and many adsorption sites. This work provided new insights to the circular utilization of tannery wastes.